Strengthening Students' Morals Through Islamic Education Concepts at MTs. Tahfidz Terpadu Anbata Medan - Siregar, Bahtiar; Nasution, Napsiah (Universitas Pahlawan Tuanku Tambusai, 2025)
Islamic education is not only oriented towards achieving cognitive aspects, but also emphasizes the formation of noble character as the main foundation of the challenges of globalization and technological developments that often influence the behavior of the younger generation, so that strengthening morals becomes a necessity. This study aims to describe and analyze the strengthening of noble character of students through the application of Islamic education concepts at MTs Tahfidz Terpadu Anbata Medan. The study uses a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and verification to obtain valid conclusions. The results of the study indicate that the application of the concept of Islamic education at MTs Tahfidz Terpadu Anbata Medan plays a significant role in forming and strengthening noble character of students. Strengthening morals is reflected through respectful attitudes towards teachers, such as getting used to greeting, smiling, and greeting, listening carefully when the teacher speaks, respecting the teacher's opinion, and following the directions given. In addition, students also show an attitude of mutual respect and respect for differences between friends. This finding confirms that Islamic education implemented in an integrated manner can be an effective instrument in building Islamic character and harmonizing social relations in the school environment.